Antagonistic actions of juvenile hormone and 20-hydroxyecdysone within the ring gland determine developmental transitions in Drosophila - Liu, Suning (Proc Natl Acad Sci U S A, 2018)
In both vertebrates and insects, developmental transition from the juvenile stage to adulthood is regulated by steroid hormones. In insects, the steroid hormone, 20-hydroxyecdysone (20E), elicits metamorphosis, thus promoting this transition, while the sesquiterpenoid juvenile hormone (JH) antagonizes 20E signaling to prevent precocious metamorphosis during the larval stages. However, not much is known about the mechanisms involved in cross-talk between these two hormones. In this study, we discovered that in the ring gland (RG) of Drosophila larvae, JH and 20E control each other’s biosynthesis. JH induces expression of a Krüppel-like transcription factor gene Kr-h1 in the prothoracic gland (PG), a portion of the RG that produces the 20E precursor ecdysone. By reducing both steroidogenesis autoregulation and PG size, high levels of Kr-h1 in the PG inhibit ecdysteriod biosynthesis, thus maintaining juvenile status. JH biosynthesis is prevented by 20E in the corpus allatum, the other portion of the RG that produces JH, to ensure the occurrence of metamorphosis. Hence, antagonistic actions of JH and 20E within the RG determine developmental transitions in Drosophila. Our study proposes a mechanism of cross-talk between the two major hormones in the regulation of insect metamorphosis.